(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
jlin √jl vkLoknuLusgu;ks%* blikf.kuh; /kkrq ls vp izR;; djus ij fu"iUu gksrk gS A O;kdj.kkRedn`f"V ls in dh O;qRifÙk bl izdkj gS & 1- ^jL;rs vkLok|rs bfr jl%*vFkkZr ftl inkFkZ dk vkLoknu fd;k tkrk gS] ogh jl gS A 2- ^jlua jl% vkLokn%* vFkkZr tks vkLoknLo:i gS] mls gh jl dgrs gSa A 3- ^jL;rs vusu bfr jl%* ftuinkFkks± ds ek/;e ls vkLokn fd;k tkrk gS] og Hkh jl dgykrk gS A